2015
DOI: 10.1002/trtr.1353
|View full text |Cite
|
Sign up to set email alerts
|

Courage to Love

Abstract: Instructional coaches continue to be an important part of school reform and professional development, and yet few studies have examined the impact of the language coaches use when working with teachers. The authors work to contribute towards filling this gap by describing a self‐;study examining their own language as instructional coaches and its impact on teachers. Paulo Freire's theories about dialogical interactions are used as a model framework. Freire outlined five conditions that must be in place to allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Li, 2016), a gap emerges in research on the role of humility in the specific area of student teaching and humility's role in mentoring or instructional coaching more broadly (e.g. Buzzanell, 2009;Jones and Rainville, 2014;Wall and Palmer, 2015). Yet, humility that led to learning was clearly present in the mentoring in the moment we examined throughout this study.…”
Section: Enacting Humilitymentioning
confidence: 95%
“…Li, 2016), a gap emerges in research on the role of humility in the specific area of student teaching and humility's role in mentoring or instructional coaching more broadly (e.g. Buzzanell, 2009;Jones and Rainville, 2014;Wall and Palmer, 2015). Yet, humility that led to learning was clearly present in the mentoring in the moment we examined throughout this study.…”
Section: Enacting Humilitymentioning
confidence: 95%
“…Although we considered this a somewhat solid plan, it turned out to be a disaster. Wall and Palmer (2015) found that "overwhelming commitments and competition for teacher time often removed the chance for deep reflection" (p. 628).…”
Section: Start Smallmentioning
confidence: 99%
“…For example, during her second school year, Alida decided to focus on just three teachers. Allen (2016) has suggested this strategy of starting a coaching initiative with a small group of teachers; many literacy coaching articles (Jones & Rainville, 2014;L'Allier et al, 2010;Wall & Palmer, 2015) also call SLPs to engage with teachers and personalize their learning. Alida chose one first-year kindergarten teacher and two teachers who had teaching experience but were new to the campus and district.…”
Section: Start Smallmentioning
confidence: 99%
“…So, how do we find time to not only begin the cycle but ensure that it remains unbroken? Wall and Palmer (2015) discussed coaching relationships using a Freirean lens. By applying Freire's conditions for dialogue, they unpacked the idea of forced collaboration between colleagues and how coaches' roles "should not be to tell the answer, provide the research, or find the solution" (p. 629).…”
mentioning
confidence: 99%